Analisa Erosivitas Lahan Pada DAS Batang Agam Dengan Menggunakan Model SWAT - Irfan Gustio -; Dwi Putri Jingga; Elvi Roza Syofyan; Chairul Muharis - (Jurnal Ilmiah Poli Rekayasa, 2020)
Batang Agam River is a river that flows along Bukittinggi City, Agam Regency, Fifty Cities Regency, Tanah Datar Regency, Payakumbuh City and empties into the Batang Sinamar River. The Batang Agam River, which crosses the residential area, is mostly used for agriculture, fisheries, tourism, mining and other activities. Community activities in the area of the Batang Agam River have resulted in a decrease in the function of the river which is characterized by narrowing, silting and pollution of the river. In addition, it is influenced by the ever-changing river water discharge, land conditions and changes that occur in the river channel. In addition, the negative behavior of the community and all their activities around the river basin also triggers damage to the river. This research was conducted to determine the value of land erosivity towards changes in land use area in the Batang Agam watershed, in this study using land cover in 2010, 2014, and 2019 using the Soil and Water Assessment Tool (SWAT) model and manual calculations were carried out using the USLE method as ratio. The analysis consists of four processes, namely watershed delineation, formation of a Hydrologic Response Unit (HRU), formation of climatological data, and finally the simulation process. The results of the HRU analysis showed that the Batang Agam watershed became 7 sub-watersheds, the dominant HRU was primary forest. In the case of Batang Agam, it was found that the level of erosion hazard was in the light category and the erosion value decreased in each review year.